An algebra problem by Yeldo Pailo

Algebra Level 4

α \alpha and β \beta are the roots of the quadratic equation λ ( x 2 x ) + x + 5 = 0 \lambda ({ x }^{ 2 }-x)+x+5=0 . If λ 1 { \lambda }_{ 1 } and λ 2 { \lambda }_{ 2 } are the two values of λ \lambda for which the roots α \alpha and β \beta are connected by the relation α β + β α = 4 \frac { \alpha }{ \beta } +\frac { \beta }{ \alpha } =4 , then find the value of λ 1 λ 2 + λ 2 λ 1 \frac { { \lambda }_{ 1 } }{ { \lambda }_{ 2 } } +\frac { { { \lambda } }_{ 2 } }{ { \lambda }_{ 1 } } .


The answer is 1022.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

James Wilson
Jan 7, 2019

Let r 1 , r 2 r_1,r_2 be the two (nonzero) roots of the general quadratic equation a x 2 + b x + c = 0 ax^2+bx+c=0 . Start by using the quadratic formula to derive the following formula: r 1 r 2 + r 2 r 1 = b 2 a c 2 \frac{r_1}{r_2}+\frac{r_2}{r_1}=\frac{b^2}{ac}-2 . Apply this formula to the given equation λ x 2 + ( 1 λ ) x + 5 = 0 \lambda x^2+(1-\lambda)x+5=0 to find α β + β α = ( 1 λ ) 2 5 λ 2 = 4 λ 2 32 λ + 1 = 0 \frac{\alpha}{\beta}+\frac{\beta}{\alpha}=\frac{(1-\lambda)^2}{5\lambda}-2=4\Rightarrow \lambda^2-32\lambda+1=0 . Applying the formula once more, one finds λ 1 λ 2 + λ 2 λ 1 = ( 32 ) 2 ( 1 ) ( 1 ) 2 = 1022 \frac{\lambda_1}{\lambda_2}+\frac{\lambda_2}{\lambda_1}=\frac{(-32)^2}{(1)(1)}-2=1022 .

Tom Engelsman
Jun 11, 2017

The above quadratic equation is expressible as:

( x α ) ( x β ) = x 2 + 1 λ λ x + 5 λ = 0 α + β = λ 1 λ , α β = 5 λ (x-\alpha)(x-\beta) = x^2 + \frac{1-\lambda}{\lambda}x + \frac{5}{\lambda} = 0 \Rightarrow \alpha + \beta = \frac{\lambda-1}{\lambda}, \alpha\beta = \frac{5}{\lambda} .

If α β + β α = 4 \frac{\alpha}{\beta} + \frac{\beta}{\alpha} = 4 holds true, then:

α 2 + β 2 α β = ( λ 1 λ ) 2 2 α β α β = ( λ 1 λ ) 2 2 5 λ 5 λ = 4 \frac{\alpha^{2} + \beta^{2}}{\alpha\beta} = \frac{(\frac{\lambda-1}{\lambda})^{2} - 2\alpha\beta}{\alpha\beta} = \frac{(\frac{\lambda-1}{\lambda})^{2} - 2\frac{5}{\lambda}}{\frac{5}{\lambda}} = 4 ,

or λ 2 32 λ + 1 = 0 λ = 16 ± 255 \lambda^{2} - 32\lambda + 1 = 0 \Rightarrow \lambda = 16 \pm \sqrt{255} .

So we finally compute:

λ 1 2 + λ 2 2 λ 1 λ 2 = ( 16 + 255 ) 2 + ( 16 255 ) 2 ( 16 + 255 ) ( 16 255 ) = 2 ( 256 + 255 ) 256 255 = 1022 . \frac{\lambda_{1}^{2} + \lambda_{2}^{2}}{\lambda_1\lambda_2} = \frac{(16+\sqrt{255})^{2} + (16-\sqrt{255})^{2}}{(16+\sqrt{255})(16-\sqrt{255})} = \frac{2 \cdot (256 + 255)}{256 - 255} = \boxed{1022}.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...